Property rights and sustainable irrigation: A developing country perspective - Meinzen-Dick, Ruth S. (Elsevier, 2014)
While the role of secure property rights contributing to sustainable natural resource management is increasingly recognized, translating that into practice is more challenging, especially in developing countries. This article presents a framework for understanding the role of property rights for effective irrigation systems and then explores the complexity of property rights to land, water, and infrastructure and their underlying institutions. Understanding property rights in practice requires acknowledging legal pluralism—the coexistence of many types and sources of law, which can be used as the basis for claiming rights over the resources. Property rights do not necessarily imply full ownership, but are composed of different bundles of rights that may be held by different claimants—the state, user groups, families, or individuals. These rights are critical for the authority, incentives, and resources for irrigation operation and maintenance. As resources become more scarce, property rights systems need to adapt to reduce conflict and provide incentives for saving water. However, efforts to improve irrigation by changing property rights systems have often failed because they have not recognized the difficulty of transplanting property rights systems from one place to another. Institutional change needs to be seen as an organic process, building on existing norms and practices, rather than as an exercise in social engineering.